DETERMINASI UKURAN PERUSAHAAN, UMUR PERUSAHAAN, PERTUMBUHAN PENJUALAN, DAN PERPUTARAN PERSEDIAAN TERHADAP KINERJA KEUANGAN - Raya Nurul Aulia; Dicky Jhoansyah; Tetty Sufianty Zafar (Journal of Economic, Bussines and Accounting (COSTING), 2026)
Manufacturing companies are one of the sectors that contribute to Indonesia's economic growth. One of its subsectors is the miscellaneous industry sector, which also supports national economic development. However, in recent years, this sector has experienced a decline in financial performance, as reflected in the decreasing Return on Assets (ROA). This study aims to examine the effect of firm size, firm age, sales growth, and inventory turnover on the financial performance of miscellaneous industry companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The research employed a quantitative method with an associative approach. The data used were secondary data in the form of financial statements of miscellaneous industry companies listed on the Indonesia Stock Exchange during the 2020–2024 period, with a sample of 21 companies selected using the purposive sampling technique. The data analysis techniques included classical assumption tests, multiple linear regression analysis, partial tests (t-tests), simultaneous tests (F-tests), and coefficient of determination tests using SPSS version 27. The results indicate that firm size has a positive and significant effect on financial performance with a significance value of 0.001 < 0.05. Firm age has a negative and significant effect on financial performance with a significance value of 0.001 < 0.05. Meanwhile, sales growth and inventory turnover do not have a significant effect on financial performance, with significance values of 0.544 > 0.05 and 0.241 > 0.05, respectively. Simultaneously, firm size, firm age, sales growth, and inventory turnover have a significant effect on financial performance with a significance value of 0.001 < 0.05.